2009
DOI: 10.1111/j.1524-4725.2008.34410.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Location and Histopathologic Subtype of Basal Cell Carcinomas in Adults Younger than 40 or 90 and Older

Abstract: A different distribution of site and subtype occurs in younger and older patients. Subtype is associated with site independent of age and sex. These findings suggest that, at least in some patients, the anatomic location of BCC may favor the development of a particular subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 24 publications
4
50
0
5
Order By: Relevance
“…This latter type was associated with lesions on the neck, trunk and limbs and with younger ages in women, which gives weight to earlier observations that this may be a type of lesion that is physiopathologically different from other types of BCC. 24,25 The superficial histological type and lesions located on the trunk were more common at younger ages only in the group of female patients. This, associated with the trend described above of an increase in the proportion of extra-cephalic lesions in this subgroup, may indicate that the risk behavior for this type of lesion, such as greater recreational exposure to the sun, particularly when the lesion is situated on the trunk, represents a more recent type of behavior in women compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…This latter type was associated with lesions on the neck, trunk and limbs and with younger ages in women, which gives weight to earlier observations that this may be a type of lesion that is physiopathologically different from other types of BCC. 24,25 The superficial histological type and lesions located on the trunk were more common at younger ages only in the group of female patients. This, associated with the trend described above of an increase in the proportion of extra-cephalic lesions in this subgroup, may indicate that the risk behavior for this type of lesion, such as greater recreational exposure to the sun, particularly when the lesion is situated on the trunk, represents a more recent type of behavior in women compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…7,9,15 Owing to their tendency for deeper invasion and an increased likelihood for perineural invasion, 16 the higher-risk types are more difficult to treat because they often involve more extensive surgery, an increased number of stages when treated with Mohs micrographic surgery, 15,17 and not all treatment modalities are suitable for such tumors. 8,18,19 The distribution of BCC by age, subtype, and anatomic distribution was recently studied by Betti et al 20 They found that younger patients are less likely to present with BCCs on the head and neck compared with elderly patients, but there was no difference in the incidence in the more aggressive subtype morpheic (morpheaform or sclerosing) BCC between the age groups. 20 Betti et al 21 revisited the concept of differential presentation of BCC by anatomic location and histologic subtype more recently and concluded that more aggressive subtypes (morpheic and infiltrative) are far more likely to present on the head and neck compared with other locations (odds ratio 4.6, 95% confidence interval 3.42-6.08).…”
mentioning
confidence: 97%
“…Morpheic BCCs were mostly on the head and neck, and prevalence did not differ between age groups. Nodular BCCs were mostly on the head and neck in older patients [11].…”
Section: Discussionmentioning
confidence: 99%